Fine root biomass and morphology in a temperate forest are influenced more by canopy water addition than by canopy nitrogen addition - Li, Wen; Wang, Chuang; Liu, Haowei; Wang, Wenqian; Sun, Ruomin; Li, Mengke; Shi, Yifei; Zhu, Dandan; Du, Wenzhi; Ma, Lei; Fu, Shenglei (Frontiers in Ecology and Evolution, 2023)
Increasing atmospheric N deposition and changes in precipitation patterns could profoundly impact forest community structure and ecosystem functions. However, most N and water (W) addition experiments have focused on direct N application to leaf litter or soil, neglecting canopy processes such as leaf evaporation and absorption. In this study, we aimed to assess the effects of atmospheric N deposition and increased precipitation on the fine root biomass and morphology of plants in a temperate deciduous forest. To achieve this, we applied N and W above the forest canopy and quantified the seasonal dynamics (January, July, and October) of fine root biomass and morphology. Our results revealed that only canopy W addition significantly increased the biomass of fine roots in January compared to that in other seasons (p < 0.05). We observed no significant interaction effect of N and W on fine root biomass. However, we found that the different growth seasons had a significant impact on the fine root biomass (p < 0.001). The combined application of N and W significantly affected the root tip density (p = 0.002). Although canopy N addition was significantly positively correlated with available soil N (p < 0.05), we detected no significant association with fine root biomass or morphology. Collectively, the findings of this study indicated that fine root biomass and morphology, are affected to a greater extent by the provision of W than by N application. These findings provide a new perspective and a more precise understanding of the effects of the actual N deposition and precipitation on the dynamics of plant fine roots in forest ecosystems.